Analisis Keterlibatan Publik dalam Pemanfaatan Instagram Untuk Komunikasi, Informasi, dan Edukasi Pengembangan Vaksin COVID-19 oleh BPOM - Dharma, Alexander Arie Sanata (Badan Pengawas Obat dan Makanan, 2023)
The COVID-19 pandemic has become a complicated problem faced by the world. The absence of specific antiviral drugs or vaccines at the beginning of the outbreak made the public health approach the primary strategy for preventing the spread of COVID-19. The lack of transparency at the start of the COVID-19 outbreak also led to public misinformation. WHO called it an infodemic, an excess of information, whether true or not, making it difficult for people to determine valid references. In Indonesia, misinformation on health matters is not a new difficulty and is in the top rank along with socio-political. The government utilizes social media to provide information to the citizens. Social media itself has a vital role in the infodemic as a medium for disseminating information, whether credible or not. The Indonesian FDA plays an essential role in conducting education through social media. This study aims to map the elements forming citizens' engagement in Indonesian FDA social media use, especially in disseminating information about the COVID-19 vaccine. This study uses a regression method with citizens' engagement (calculated from the number of likes and comments) as the dependent variable. Three independent variables form citizen engagement elements: media richness, content production, and content type defined by the government. The sentiment toward government Instagram posts was measured by analyzing citizens' comments using the dataset from InSet Semantic Lexicon. Based on negative binomial regression results, data obtained that the framework developed in this research was statistically significant in observing the phenomenon. Media richness and content production significantly affect citizens' engagement. On the other hand, original and informative content encourages more citizen engagement. Generally, public sentiment on Indonesian FDA Instagram content, both head office and regional offices, tends to be more positive than negative.